Label-free protocol to quantify protein affinity using isothermal titration calorimetry and bio-layer interferometry of a human eIF5-mimic protein - Chingakham Ranjit Singh; Rahul Jaiswal; Carlos R. Escalante; Katsura Asano (STAR Protocols, 2022)
Summary: eIF5-mimic protein (5MP) controls translation through its interaction with eukaryotic translation initiation factor (eIF) 2 and eIF3 and alters non-AUG translation rates for oncogenes in cancer and repeat expansions in neurodegenerative disease. To precisely evaluate the effect of 5MP mutations on binding affinity against eIFs, here we describe two label-free protocols of affinity measurement for 5MP binding to eIF2 or eIF3 protein segments, termed isothermal titration calorimetry (ITC) and bio-layer interferometry (BLI), starting with how to purify proteins used.For complete details on the use and execution of this protocol, please refer to Singh et al. (2021). : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.